Hipotiroid Kongenital - Ida Bagus Eka Utama Wija; Christine Handayani Tampubolon (CV. Inara, 2026)
Congenital hypothyroidism (HK) is the most common congenital endocrine disorder in children and is the most common cause of preventable mental retradation. The disorder is caused by the absence of thyroid hormones in the womb and is not needed early can cause severe mental retardation. Clinical manifestations in neonates are not specific, but manifestations obtained after birth consist of gestational age> 42 weeks, BBL> 4kg jaundice> 3 days after birth, edema, umbilical hernia, macroglossia, acrocyanosis. The diagnosis can be made for thyroid screening. Thyroid screening in neonates is carried out before being discharged from the hospital, from the 2nd to 4th day of the baby's age, by checking TSH and T4 levels. The dose of the thyroxine hormone is adjusted to the baby's age and also the baby's body weight.